Oxidative etching mechanism of the diamond (100) surface. (15th April 2021) - Enriquez, John Isaac; Muttaqien, Fahdzi; Michiuchi, Masato; Inagaki, Kouji; Geshi, Masaaki; Hamada, Ikutaro; Morikawa, Yoshitada
Abstract: We performed density functional theory calculations with van der Waals corrections to elucidate diamond oxidation mechanism on the atomic-level which could lead to insights that will advance the improvement of nascent nanofabrication technologies. We developed a comprehensive theory of oxidative etching of the diamond (100) surface, from the adsorption of gas phase O2, including details of metastable adsorption states, intersystem crossing, and induced surface dereconstruction, to the desorption of CO and CO2, complete etching of the top surface layer and its subsequent stabilization. Oxygen adsorption induce C-dimer bond breaking through the formation of carbonyl structures at low surface coverage. At high surface coverage, adjacent carbonyls can transform into the more stable ether chain with small energy barrier requirement. A mix of carbonyl and ether will form in surfaces with defects, and several models of possible structures have been presented. CO desorption creates a point defect that serves as nucleation site for the preferred etching direction along [011], perpendicular to the top layer C-dimer bonds. We obtained a wide range of desorption activation energies, which depend on the existence of point defects and reconstruction of surfaces. C-dimer formation and oxygen adsorption stabilize vacancies and single-atomic-layer-deep trough. Graphical abstract: Image 1